Efficient Chromatic-Number-Based Multiqubit Decoherence and Crosstalk Suppression - Amy F. Brown; Daniel A. Lidar (PRX Quantum)
The performance of quantum computers is hindered by decoherence and crosstalk, which cause errors and limit the ability to perform long computations. Dynamical decoupling is a technique that alleviates these issues by applying carefully timed pulses to individual qubits, effectively suppressing unwanted interactions. However, as quantum devices grow in size, it becomes increasingly important to minimize the time required to implement dynamical decoupling across the entire system. Here, we present “chromatic Hadamard dynamical decoupling” (CHaDD), an approach that efficiently schedules dynamical decoupling pulses for quantum devices with arbitrary qubit connectivity. By leveraging Hadamard matrices, CHaDD achieves a circuit depth that scales linearly with the chromatic number of the connectivity graph for general two-qubit interactions, assuming instantaneous pulses. This includes ZZ crosstalk, which is prevalent in superconducting quantum processing units (QPUs). The scaling of CHaDD represents an exponential improvement over all previous multiqubit decoupling schemes for devices with connectivity graphs the chromatic number of which grows at most polylogarithmically with the number of qubits. For graphs with a constant chromatic number, the scaling of CHaDD is independent of the number of qubits. We report on experiments we have conducted using IBM QPUs that confirm the advantage conferred by CHaDD. Our results suggest that CHaDD can become a useful tool for enhancing the performance and scalability of quantum computers by efficiently suppressing decoherence and crosstalk across large qubit arrays.